الإغتراب الوظيفي وأثره على أداء العاملين دراسة حالة بمؤسسة توزيع الكهرباء والغاز الأغواط - بن دومة مريم; عرباوي سارة; عبد العالي بشير (جامعة عمار ثليجي الاغواط, 2022)
The aim of the study was to identify the phenomenon of job alienation and its impact on the performance of workers of the Electricity and Gas Distribution Corporation in oats in terms of its causes, effects and ways of confronting it. In order to achieve the objectives of the study, a random sample of the Sonelgas workers' group of various levels was adopted, consisting of 50 questionnaires. In the light of the statistical analysis of the study's identification, the results of the study revealed that the distinction between workers and their lack of participation in decision-making were among the most significant forms of employee suffering resulting from the phenomenon of job alienation, while the lack of credibility and transparency of performance reports and the failure to take into account careful specialization in work performance were among the leading causes of the phenomenon of employment alienation.